Авторська колонка: проблеми жанрової ідентифікації - Калинюк, Христина (Видавництво Львівської політехніки, 2012)
The article is devoted to identification of the main characteristics and features of the column as a publicistic genre, finding its place in the system of genres.
Keywords: column; genre; author; publicism; characteristics; columnism